â€œNur Muhammadâ€ dalam Naskah Klasik Gorontalo - Sofyan A. P. Kau (Al-Ulum, 2011)
â€œNur Muhammadâ€ is a popular concept in the discourse of Sufism falsafati. In Gorontalo, texts of Muhammad Nur iw widely known. The texts, as the author of the findings gathered in a collection of manuscripts under the theme "Israâ€™ Miâ€™raj". Because it is a manuscript on Nur Muhammad is a commonly red each month of Rajab, exactly 27 Rajab regarding event-Isra Mi'raj. This paper shows that the manuscript Gorontalo Nur Muhammad is not the original work of local scholars Gorontalo, but it is a re-adaptation and copy the text of Nur Muhammad Classical Malay. This assumption is based on text analysis, and comparison with historical texts (manuscripts) others, as well as socio-cultural analysis of the Muslim community that mentradisikan Gorontalo reading the manuscripts on Islamic day events.